Rapid in‐field failures following adjuvant radiation for buccal squamous cell carcinoma. (25th April 2019) - Factor, Oren; Su, William; Lazarev, Stanislav; Miles, Brett; Genden, Eric; Sharma, Sonam; Gupta, Vishal; Misiukiewicz, Krzysztof; Bakst, Richard L.
Abstract : Objectives/Hypothesis: Squamous cell carcinoma originating in the buccal mucosa and retromolar trigone (RMT) have historically poor outcomes. Difficulties in discriminating tumor origin often result in these subsites being combined in surgical and pathological reports. We aimed to determine if making this anatomical distinction has implications for treatment design and clinical outcomes. Study Design: Retrospective case series. Methods: We identified 27 tumors from either the buccal mucosa patients or RMT patients who underwent surgery followed by radiation. For patients who developed a local failure, we fused the pretreatment imaging, simulation computed tomography, and follow‐up imaging to determine the location of failures relative to the radiation field. We calculated the 2‐year locoregional control and 2‐year disease‐free survival. Results: The median time from surgery to radiation was 50 days (range, 32–133 days). The 2‐year locoregional control for buccal mucosa versus RMT, respectively, were 35.9% versus 68.4% ( P = .252). The 2‐year disease‐free survival rates were 32.7% versus 68.4%, respectively ( P = .196). The median times to failure were 12.00 months (range, 4.9–115.0 months) versus 18.5 months (range, 4.5–61.0 months), respectively. All buccal mucosa failures occurred within the high‐dose planning target volume, with a median dose of 60 Gy within the failure region. Following locoregional failure, 10 of the 12 patients have died, with a median time from local failure to death of 3.6 months (range, 1–17.6 months). Conclusions: Squamous cell carcinomas of the buccal mucosa appear to have a poor prognosis characterized by rapid in‐field failure. Therefore, differentiating tumor origin may be important for prognostication and treatment. Level of Evidence: 3 Laryngoscope, 130:413–417, 2020